Effect of Disinfectants on the Hardness of Dental Stones - Elnaz Moslehifard; Farzad Nasirpouri; Sanaz Gasemzadeh (Islamic Dental Association of Iran, 2013)
Background and Aim : Considering the risk of cross contamination, disinfection of dental stones is essential provided that their mechanical and structural properties remain unchanged. The aim of this study was to evaluate the effect of disinfection on the hardness of dental stones .   Materials and Methods : In this experimental study, 40 discs were fabricated of type III and IV dental stones and divided into three groups. The three understudy chemical disinfectants namely 1% Virkon, 0.525% hypochlorite and slurry water were sprayed on samples in each group. The hardness of sprayed samples was evaluated by measuring the width of scratch according to the Mohs scale of mineral hardness. Surfaces of sprayed samples were also inspected by optical microscopy. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests (P<0.05 ).   Results : Mohs scale of mineral hardness revealed that the width of scratches was narrower in samples sprayed with Virkon than in those sprayed with hypochlorite and slurry water. In type III dental stone specimens, the maximum width was observed in samples sprayed with slurry water (1.35±0.02) and the minimum width was observed in Virkon group samples (0.97±0.01). For type IV, the maximum and minimum widths were observed in samples sprayed with slurry water (1.20±0.01) and Virkon (0.61±0.01), respectively . In both types of stones, no significant differences were noted between the sprayed groups, while the differences between each sprayed group and the control stones (no spraying) were significant .   Conclusion : Surface hardness of dental stones decreased after spraying them with the three understudy disinfectants. Dental stones sprayed with Virkon exhibited the lowest reduction in hardness .